2005
DOI: 10.1155/2005/796963
|View full text |Cite
|
Sign up to set email alerts
|

A Point Mutation in the Iron-Responsive Element of the L-Ferritin in a Family with Hereditary Hyperferritinemia Cataract Syndrome

Abstract: The combination of early-onset cataracts and an elevated ferritin level should suggest this genetic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Prior reports on HHCS have originated from Western Europe, 1,2,4-15 North America, [16][17][18][19][20] Australia, 21,22 and India. 23 These studies have also shown that distinct chromosomal mutations in the iron responsive element of the L-ferritin subunit are responsible for HHCS; these mutations prevent binding of iron (which provides negative feedback) and lead to the unregulated production of ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…Prior reports on HHCS have originated from Western Europe, 1,2,4-15 North America, [16][17][18][19][20] Australia, 21,22 and India. 23 These studies have also shown that distinct chromosomal mutations in the iron responsive element of the L-ferritin subunit are responsible for HHCS; these mutations prevent binding of iron (which provides negative feedback) and lead to the unregulated production of ferritin.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HHCS do not develop iron overload, although common HFE mutations, especially H63D, may occur in HHCS patients coincidentally. L-ferritin deposition in the ocular lens causes bilateral cataracts at an early age [15][16][17]. It may be possible to have an elevated ferritin on this basis without cataracts [18].…”
Section: Assessment Of Patients With An Elevated Ferritin Concentratimentioning
confidence: 99%
“…Examples of specific recognition motifs are TAR (Richter et al 2002) and RBE (RRE) (Hung et al 2000;Lesnik et al 2002) motifs of HIV-1 and the IRE motifs found in mRNAs related to iron metabolism (Theil, 2000 ;Pantopoulos, 2004). Many riboregulators, riboswitches, and aptamers form potentially highly structured regions for protein or small molecule interaction, and mutations in these structures may result in a loss of regulation and a corresponding disease state (Sobczak & Krzyzosiak, 2002 ;Wong et al 2005). In the remainder of this review we will focus on general RNA structural motifs, their identification, classification, types, and roles.…”
Section: Specific Recognition Motifsmentioning
confidence: 99%